2014
DOI: 10.1210/en.2013-1667
|View full text |Cite
|
Sign up to set email alerts
|

Bilirubin Increases Insulin Sensitivity in Leptin-Receptor Deficient and Diet-Induced Obese Mice Through Suppression of ER Stress and Chronic Inflammation

Abstract: Obesity-induced endoplasmic reticulum (ER) stress causes chronic inflammation in adipose tissue and steatosis in the liver, and eventually leads to insulin resistance and type 2 diabetes (T2D). The goal of this study was to understand the mechanisms by which administration of bilirubin, a powerful antioxidant, reduces hyperglycemia and ameliorates obesity in leptin-receptor-deficient (db/db) and diet-induced obese (DIO) mouse models. db/db or DIO mice were injected with bilirubin or vehicle ip. Blood glucose a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
98
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(111 citation statements)
references
References 56 publications
6
98
0
2
Order By: Relevance
“…Biliverdin and bilirubin are both potent antioxidants through a direct ROS scavenging mechanism and were found to prevent oxidative stress-mediated cell death [50]. Recently, bilirubin was shown to enhance insulin signalling response in a diet-induced obesity mouse model an in db/db diabetic mice through the suppression of ER stress response [51]. Bilirubin levels in humans were found to be associated with reduced risk for coronary heart disease [50,52].…”
Section: Discussionmentioning
confidence: 99%
“…Biliverdin and bilirubin are both potent antioxidants through a direct ROS scavenging mechanism and were found to prevent oxidative stress-mediated cell death [50]. Recently, bilirubin was shown to enhance insulin signalling response in a diet-induced obesity mouse model an in db/db diabetic mice through the suppression of ER stress response [51]. Bilirubin levels in humans were found to be associated with reduced risk for coronary heart disease [50,52].…”
Section: Discussionmentioning
confidence: 99%
“…43 Bilirubin also ameliorates insulin sensitivity through the inhibitory properties of endoplasmic reticulum stress and inflammation. 44 Thus, bilirubin might exert its protective action through multiple mechanisms in addition to the antioxidant property.…”
Section: Discussionmentioning
confidence: 99%
“…Dong et al (8) demonstrated that BR administration improved hyperglycemia and obesity by increasing insulin sensitivity. It has been widely reported that HO-1 upregulation protected pancreatic islet cells from apoptosis, and improved their functions in vivo (27).…”
Section: Discussionmentioning
confidence: 99%